Effects of Online Health Information Seeking Behavior on Academic Determination as Mediated by Mental Toughness Confidence Clustered by Academic Year Level: A Multilevel Analysis - Balila, Edwin A.; Guanco, Rhalf Jayson F.; Castillo, Sheryll Ann M. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Multilevel analysis has become one of the most extensively used means to investigate ways by which variables are affecting each other. Multilevel analysis is useful for data that are hierarchical in nature. Thus, this study employs multilevel mediation methods since data is fully nested. This also utilizes 813 college students participating from selected educational institutions in the Philippines during the academic year 2020-2021, with ages 18 years old and above and with academic level from the first year to the fifth year. It focuses on mental toughness as a mediator and investigates why academic determination would be affected by online health information-seeking behavior at the individual level and at different academic year levels using multilevel mediation analysis. The results of the study showed that the within-effects of both direct and indirect effects of the structural model are significant at the α = .01 level. This means that on the individual level (or level 1), mental toughness confidence is partially mediating the effects of online health-seeking behavior on the academic determination. However, when between-effects are considered, both direct and indirect effects were found to be not significant. This implies that when respondents are clustered by academic year level (level 2), both direct and indirect effects are not significant. Hence even across academic year levels, mental toughness confidence is partially mediating the influence of online health-seeking behavior on the academic determination. Keywords : mediation, multilevel analysis, health information-seeking behavior, mental toughness, confidence, academic determination